2009
DOI: 10.1155/2009/535643
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Antimicrobial Screening of Alkaloid Fractions from Strychnos potatorum

Abstract: Alkaloid fractions isolated fromStrychnos potatorumL.f. (Loganiaceae) seed were tested for their antimicrobial properties against some pathogenic gram positive, gram negative and acid-fast bacteria and fungi. These fractions have shown considerable antimicrobial activity against both bacteria and fungi at the tested concentrations (100 & 200 μg/mL). Further, the growth ofProteus vulgaris, taphylococcus aureus, Salmonella typhimurium, Vibrio cholerae, Mycobacterium tuberculosis, Aspergillus nigerandCandida … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…The results of LC-MS/MS experiment indicated toon leaves fraction 5 contains N-[2-(D-Glucopyranosyloxy)ethyl]-2-hydroxy-N-[2hydroxy3 (octadecyloxy) propyl]butanamide and Brucine which may relate to the antifungal properties of the fraction 5 (Figure 3). Mallikharjuna and Seetharam (2009) reported that Brucine compound had antifungal activity against A. niger, A. fumigatus, C. albicans and M. gypseum fungi.…”
Section: Discussionmentioning
confidence: 99%
“…The results of LC-MS/MS experiment indicated toon leaves fraction 5 contains N-[2-(D-Glucopyranosyloxy)ethyl]-2-hydroxy-N-[2hydroxy3 (octadecyloxy) propyl]butanamide and Brucine which may relate to the antifungal properties of the fraction 5 (Figure 3). Mallikharjuna and Seetharam (2009) reported that Brucine compound had antifungal activity against A. niger, A. fumigatus, C. albicans and M. gypseum fungi.…”
Section: Discussionmentioning
confidence: 99%
“…Other Strychnos species have however been shown to display antimicrobial activity. For example, S. potatorum exhibited inhibitory action against Gram positive bacteria such as S. aureus, and Gram negative bacteria like Proteus vulgaris, S. typhimurium and Vibrio cholerae (Mallikharjuna and Seetharam, 2009 (Gnanavel et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…It can be used for clarification of turbid water 81 . It also has metal binding properties 82 and antimicrobial properties 83 .…”
Section: Chemical Constituentsmentioning
confidence: 99%